The Role of Financial Behaviour in Improving Financial Literacy: A Study of Indonesian Students Abroad - Ardiansyah Rasyid; Antonia Devina Natasha; Ruth Serafina Dharmawan; Richardo Tan; Stevhen Tjiontara (Sultan Publisher, 2026)
Financial literacy is a crucial competence in navigating the increasing complexity of the modern global economy, particularly for students studying abroad who must manage their finances independently. This study aims to analyze the influence of financial knowledge, financial attitude, and financial behavior on the financial literacy of Indonesian students studying overseas. A quantitative approach was employed using a survey method involving 50 respondents selected through purposive sampling. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using SEM-PLS. The results indicate that financial behavior has a positive and significant effect on financial literacy, whereas financial knowledge and financial attitude do not show significant effects. The coefficient of determination (R² = 0.818) suggests that the model has strong explanatory power. These findings highlight the importance of practical financial behavior over theoretical knowledge and attitudes in improving financial literacy. This study contributes to the literature by emphasizing the existence of a knowledge–behavior gap and underlining the need for practice-oriented financial education to enhance sustainable financial literacy among students.